Primary amenorrhoea: Swyer syndrome in a woman with pure 46XY gonadal dysgenesis and late presentation - Andreas Chrysostomou (South African Medical Association, 2015)
Simple 46,XY gonadal dysgenesis, also called Swyer syndrome, is a very rare condition, estimated to occur in approximately 1/100 000 people. The condition first becomes apparent in adolescence, with delayed puberty and primary amenorrhoea. This is a case study of a patient who presented with primary amenorrhoea and primary infertility. She was a 24-year-old phenotypically female patient with a delayed diagnosis of Swyer syndrome.